Consumer adoption of m-commerce: Motivations for high involvement product purchase - Swati Mehta (International Journal of Advanced Science and Technology, 2020)
Mobile technology has made shopping even more convenient and has also provided lasting advantages for companies to meet consumer needs. The power of a smartphone to access a customer anywhere and anywhere lets businesses provide on-the-go services to consumers. It comes with a requirement to make the journey of shopping even more rewarding and personalized. As people purchase with different shopping objectives, this may lead to vastly different buying habits. This study aims to establish the underlying motivations and perceived risks for using the mobile shopping platforms. This will help retailers proactively improve their mobile shopping services.Among various product categories, high involvement products like laptop, mobile phone, television etc. is taken into account for the research purpose. Reason being that this category is perceived as a high-stake category. Purposive sampling method is taken for data collection. Questionnaire was prepared considering 15 different factors. After exploratory factor analysis, 5 major factors were obtained; monetary benefits and risks, psychological factors, product satisfaction related factors, convenience related factors and brand image related factors.Keywords: M-commerce, consumer behavior, mobile- technology, shopping motivations, perceived risks.